2013
DOI: 10.3920/wmj2012.1510
|View full text |Cite
|
Sign up to set email alerts
|

Vip3Aa and Cry1Ab proteins in maize reduceFusarium ear rot and fumonisins by deterring kernel injury from multiple Lepidopteran pests

Abstract: Field trials were conducted in 2008, 2009 and 2011 to assess fumonisin contamination in transgenic (Bt) and non- Bt maize hybrids infested with European corn borer, corn earworm, and Western bean cutworm. Comparisons were made among maize hybrids expressing two transgenic insect resistance proteins (Cry1Ab × Vip3Aa), a single resistance protein (Cry1Ab), or no insect resistance. The field design was a randomised complete block design with four replicates of each hybrid × insect combination. Kernel injury, Fusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Our results parallel those of others examining WBC and its association with ear rots. In one study, Bowers et al found similar trends, whereby greater kernel injury attributed to WBC (and other ear‐feeding Lepidoptera) led to increased levels of Fusarium ear rot and subsequent higher levels of fumonisins in grain. Importantly, both of these studies were focused chiefly upon quantifying Bt hybrid treatment differences with respect to the presence of Cry toxins targeting lepidopteran pests, and in both cases it was demonstrated that targeting larvae with these hybrids effectively reduced the incidence of the disease and mycotoxins.…”
Section: Discussionmentioning
confidence: 86%
“…Our results parallel those of others examining WBC and its association with ear rots. In one study, Bowers et al found similar trends, whereby greater kernel injury attributed to WBC (and other ear‐feeding Lepidoptera) led to increased levels of Fusarium ear rot and subsequent higher levels of fumonisins in grain. Importantly, both of these studies were focused chiefly upon quantifying Bt hybrid treatment differences with respect to the presence of Cry toxins targeting lepidopteran pests, and in both cases it was demonstrated that targeting larvae with these hybrids effectively reduced the incidence of the disease and mycotoxins.…”
Section: Discussionmentioning
confidence: 86%
“…Inverse results were observed for the hybrid Attack, which presented low incidence of kernel rot and higher levels of fumonisin in the grains. Although F. verticillioides and fumonisins may be found in asymptomatic corn grains (Lanza et al 2017), high levels of fumonisins are commonly associated with ear rot incidence (Bowers et al 2013). According to Parsons and Munkvold (2010), grains showing physical injuries have a higher incidence of ear rot and contamination with fumonisins than undamaged grains.…”
Section: Discussionmentioning
confidence: 99%
“…According to Parsons and Munkvold (2010), grains showing physical injuries have a higher incidence of ear rot and contamination with fumonisins than undamaged grains. In particular, insect-damaged grains are more likely to be contaminated with fungi and mycotoxins (Bowers et al 2013). According to these authors, the use of transgenic hybrids expressing the Cry1AB x Vip3Aa genes reduced the fumonisin content in the grains when compared to hybrids expressing only the Cry1AB gene or non-transgenic hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, biotechnology developers are stressing the use of insecticidal proteins other than Cry1Ab, or using newer traits together with Cry1Ab, in combinations that provide resistance to the full range of Lepidopteran pests. Fumonisin levels in these hybrids have been extremely low in field trials (Bowers et al, 2013), and they show increased capacity to reduce aflatoxin levels as well.…”
Section: Managing Mycotoxins Pre-and Post-harvestmentioning
confidence: 99%